Otomatisasi Pengujian Aplikasi POS (Point Of Sale) Menggunakan Metode White Box - Amin Andriyanto; Apriansyah; Auransyah Sekar Pratiwi; Iqbal Nurdiansyah; Aries Saifudin (CV. Multi Kreasi Media, 2023)
Point of sale (POS), or what is often called POS, is a system in the business world that uses hardware and software. This POS system has key features such as adding transactions, viewing sales transaction history and sales progress graphs, estimating revenue, and identifying sales which includes a list of best selling products and product combinations. Testing of this application was carried out using the white box method for two weeks after the program was finished. The result of implementing the POS application is a web application for sales orders that makes it easy to manage goods and recap monthly or annual transactions. In evaluating application compatibility and compatibility with the database, this application is implemented for one week to check whether there are still problems or not. As long as the program is approved, improvements and adjustments will be made according to the needs of stores that will use this POS application. Based on the research conducted, it can be concluded that the Point of Sale (POS) information system created can be used by users.